Estrategias de enseñanza para el desarrollo de la creatividad en los niños - Cereghino Cabrera, Brunella (2016)
The present article searches to identify and describe the common bases of those pedagogical procedures that stimulate creativity. We believe that training creative people, who adapt to changing contexts that are able to get information at  their fingertips and apply it differently is a necessity in this century. Educating children who are creative and capable of solving problems by themselves is not an easy task, it requires educators to seek a methodology that allows them to carry out ateaching - learning process which stimulates creativity within the subject they are responsible for.